Eye-readable gasochromic and electrical detectability of hydrogenated Pd-TiO 2 to gaseous fluorine species - Shim, Gowoon; Lee, Sang Yeon; Kalanur, Shankara S.; Seo, Hyungtak (Applied Surface Science, 2018)
Fluorine-containing gases (e.g., CF 4 , SF 6 , and XeF 2 ) are utilized in various industrial processes. However, these gases are toxic and detection of their leakage is crucial for safety reasons. In this study, the detection mechanism of a fluorine-containing gas is provided by hydrogenated palladium loaded on titanium dioxide (Pd-TiO 2 ) upon XeF 2 gas exposure. The color of the Pd-TiO 2 nanocomposite changed from light gray to dark gray after hydrogen annealing. When the Pd-TiO 2 was exposed to XeF 2 gas, the initial light gray color was restored. The reflectance of Pd-TiO 2 increased from 15% to 30% after XeF 2 treatment. Incorporation of H and F resulted in an increase in the intensity of Ti 3+ signal in EPR and a change in the sub-gap electronic state, identified using UV–vis spectroscopy, with H 2 and XeF 2 gas treatment of bulk TiO 2 . A physiochemical model and electronic band structure is suggested by based on these results as well as XPS results for the reaction and gasochromic mechanism. The results also indicate electrical response of Pd-TiO 2 to F sensing at 100 of conductance ratio of sensing to standby condition, suggesting the possibility of bimodal gaseous F detection.
Keywords: Bimodal; Detection mechanism; Electrical response; Electronic band structure; Gaseous fluorine species; Gasochromic; Hydrogenated; Physiochemical models; Bimodal; Gaseous fluorine; Gasochromic; Hydrogenated; Palladium loaded titanium dioxide